PENGARUH INFORMASI LAPORAN ARUS KAS TERHADAP VOLUME PERDAGANGAN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERCATAT DI BURSA EFEK INDONESIA - YAZID AL BASTOMI, AHMAD Yazid (Jurnal Akuntansi AKUNESA, 2014)
This study aimed to determine the effect of cash flow statement information for trading volume. The sample in this study are food and beverage companies on the Indonesia Stock Exchange in 2011-2013. The total number of samples are 16 companies with the number of observations 48 pieces. The analysis used multiple linear regression which using the classical assumption, coefficient determination, t test, and f test. The dependent variable in this study is the trading volume activity and the independent variable is the cash flow statement consists of operating cash flow (AO), investment cash flow (AI), financing cash flow (AP) and the total cash flow.The results showed that the investment cash flows have an impact on trading volume. However, operating cash flow, financing cash flow, and the total cash flow has no effect. This shows that not all information cash flows can be used by investors as a basis for making investment decisionsKeyword : cash flow reporting, trading volume activity, food and beverage